Alpha to Omicron: Disease Severity and Clinical Outcomes of Major SARS-CoV-2 Variants. (10th October 2022) - Esper, Frank P; Adhikari, Thamali M; Tu, Zheng Jin; Cheng, Yu-Wei; El-Haddad, Kim; Farkas, Daniel H; Bosler, David; Rhoads, Daniel; Procop, Gary W; Ko, Jennifer S; Jehi, Lara; Li, Jing; et al.
Abstract: Background: Four severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants predominated in the United States since 2021. Understanding disease severity related to different SARS-CoV-2 variants remains limited. Method: Viral genome analysis was performed on SARS-CoV-2 clinical isolates circulating March 2021 through March 2022 in Cleveland, Ohio. Major variants were correlated with disease severity and patient outcomes. Results: In total 2779 patients identified with either Alpha (n = 1153), Gamma (n = 122), Delta (n = 808), or Omicron variants (n = 696) were selected for analysis. No difference in frequency of hospitalization, intensive care unit (ICU) admission, and death were found among Alpha, Gamma, and Delta variants. However, patients with Omicron infection were significantly less likely to be admitted to the hospital, require oxygen, or admission to the ICU (χ 2 = 12.8, P < .001; χ 2 = 21.6, P < .002; χ 2 = 9.6, P = .01, respectively). In patients whose vaccination status was known, a substantial number had breakthrough infections with Delta or Omicron variants (218/808 [26.9%] and 513/696 [73.7%], respectively). In breakthrough infections, hospitalization rate was similar regardless of variant by multivariate analysis. No difference in disease severity was identified between Omicron subvariants BA.1 and BA.2. Conclusions: Disease severity associated with Alpha, Gamma, and Delta variants is comparable while Omicron infections are significantly less severe. Breakthrough disease is significantly more common in patients with Omicron infection. Abstract : Four SARS-CoV-2 variants predominated in the United States since 2021. Disease severity associated with Alpha, Gamma, and Delta variants were comparable while Omicron infections are significantly less severe. Additionally, no differences in Omicron subvariant severity (BA1 vs BA2) were identified.